Quality Assessment of Compost from Laboratory Reactor by Germination Index - Thien-Phuc Nguyen; Mitsuhiko Koyama; Kiyohiko Nakasaki (Journal of Technical Education Science, 2024)
Composting is a useful waste treatment for environmental problem, but composting experiment is challenging due to large-scale requirement. Thus, laboratory-scale reactor is of interest for composting experiment. The capability of laboratory-scale reactor to simulate large-scale composting was determined by assessing the quality of produced compost via germination index. The laboratory-scale reactors were set up from mini-reactor (internal volume 101 mL) with fixed temperature inside an incubator and two air flow rates (5.5 mL/min, 1.375 mL/min). Rabbit food was chosen as model food waste for reproducible results. During the course of the experiment, the progress of CO2 evolution rate from laboratory-scale composting was similar to that of large-scale composting. After 10 days of composting, both air flow rates produced compost with organic matter degradation more than 70%. Throughout the course of the composting, sample was collected for germination index test. The germination index test showed that raw materials did undergo transformation to become less phytotoxicity. The germination index of final product was higher than 60%, indicating a matured and stabled compost. Thus, the composting in laboratory-scale system can simulate the progress in large-scale composting.